PENYELENGGARAAN SISTEM PRESIDENSIL BERDASARKAN KONSTITUSI YANG PERNAH BERLAKU DI INDONESIA - S, Laurensius Arliman (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2019)
A presidential system government is a government in which the executive position is not accountable to the representative body of the people, in other words the executive power is outside (direct) parliamentary oversight. Not only is presidentialism and a multiparty system a